Randomised comparison of vascular response to biodegradable polymer sirolimus eluting and permanent polymer everolimus eluting stents: An optical coherence tomography study - Koppara, Tobias; Tada, Tomohisa; Xhepa, Erion; Kutner, Sebastian; Byrne, Robert A.; Ibrahim, Tareq; Laugwitz, Karl -Ludwig; Kastrati, Adnan; Joner, Michael (International Journal of Cardiology, 2018)
Background: Drug-eluting stents with biodegradable polymer coatings have shown promising outcomes in randomised studies. Methods: We compared neointimal healing patterns including strut coverage and assessed neointimal maturity using a novel algorithm in coronary lesions treated with sirolimus-eluting stents with biodegradable polymer coating (BP-SES) or everolimus eluting stents with permanent polymer coating (PP-EES) using optical coherence tomography after 6 months. Results: A total of 39 patients were randomised to BP-SES (n = 19) or PP-EES (n = 20) for the treatment of coronary lesions. Of those, 29 patients (14 BP-SES and 15 PP-EES) underwent optical coherence tomography (OCT) and angiography at 6-month follow-up. Tissue coverage and apposition were assessed in a total of 6162 struts (BP-SES, n = 2889; PP-EES, n = 3273). Neointimal maturity was assessed in 3672 neointimal regions above struts using grey scale intensity analysis. OCT analysis showed neointimal coverage of 2433 (BP-SES) vs. 2702 (PP-EES) struts (84.2% vs. 82.6%, p = 0.70), whereas the remainder was uncovered after 6 months. Mean neointimal thickness did not differ significantly between groups (54.3 ± 7.8 μm vs. 80 ± 14.6 μm, p = 0.12). The rate of malapposed struts was comparable between groups (1.3% vs. 2.2%, p = 0.27). Grey scale signal intensity analysis showed mature tissue coverage of struts in 46.2% in BP-SES vs. 31.8% in PP-EES (p = 0.31) of neointimal regions. Conclusion: The present study showed comparable early vascular healing response characterised by neointimal coverage with mainly immature neointima in both BP-SES and PP-EES.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Biodegradable polymer coating; Optical coherence tomography; Percutaneous coronary intervention